Lifestyle treatments in cystic fibrosis: The NHS should not pay. (August 2016) - Hull, Jeremy
Summary: Lifestyle treatments can be defined as those which may have in impact on quality of life but do not affect health outcomes. Particular treatment options may be preferred by patients because they are for example, easier to use, take up less time or taste better. The impact on adherence needs to be considered. Treatment options that promote greater adherence to therapy are likely to be more efficacious and so are not, by definition, lifestyle treatments. The NHS is facing unprecedented financial pressure and resources are limited. When lifestyle treatments are more expensive than standard therapy, they should not be funded by the NHS.